Assessment of Soil Nutrient Testing using IoT-based Smart Farming Application for the Application of Organic Liquid Fertilizer from Saccharum officinarum Linn. Extract and Hevea brasiliensis Muell. Arg. Extract on Ultisol Soil Media - Erwin Junaidi Lubis (Jurnal Agroteknologi dan Inovasi Pertanian, 2026)
In the world of agriculture, the economy of production is very important to maintain and must be developed through the application of smart farming technology. The smart farming technology referred to here is the Internet of Things (IoT), which is applied in the form of sensors, actuators, humidity monitoring, hydrogen potential (pH), and soil nutrient levels. Research results show that IoT-based smart farming technology has proven to be very effective in monitoring soil health and supporting agricultural progress. In the results of field research using modern IoT-based smart farming technology, soil acidity (pH) reached a success rate of 94.20% or 0.15. Irrigation and the application of other soil chemicals were included in the automatic technology design and proved to be very effective in observing and identifying the nutrient deficiency of Ultisol soil. With the help of liquid organic fertilizers, Saccharum officinarum Linn. extract and Hevea brasiliensis Muell. Arg. extract greatly supported the health and fertility of Ultisol soil through the resulting sensory data.